Effects of Chemical Insecticide Residues and Household Surface Type on a Beauveria bassiana-Based Biopesticide (Aprehend(®)) for Bed Bug Management - Shikano, Ikkei (Insects, 2021)
SIMPLE SUMMARY: Aprehend is a novel fungal biopesticide for the control of bed bug infestations. The formulation consists of fungal spores of the entomopathogen, Beauveria bassiana suspended in a proprietary oil formulation. Bed bug infestations are commonly treated with chemical insecticides and can require multiple applications to achieve eradication. The goal of this study was to determine if the presence of previously applied chemical insecticide residues would impact the efficacy of Aprehend when applied on top of chemical residues. A series of experiments was conducted by applying Aprehend on top of dried residues of 22 chemical insecticides on different surface types (fabric and wood). We found that residues of eight of the pesticides evaluated did not impact viability of the fungal spores in comparison to the control. Further evaluation of the effect of chemical residues on bed bug mortality revealed that chemical residues on fabric surfaces had less detrimental impact than those on wood. It is concluded that the practical implication of the presence of old chemical residues will have a minimal impact on overall control. ABSTRACT: The biopesticide Aprehend, containing spores of the entomopathogenic fungus Beauveria bassiana, is a biological control agent for the management of the common bed bug (Cimex lectularius L.) (Hemiptera: Cimicidae). The spores are applied in strategically placed barriers, which bed bugs walk across as they search for a bloodmeal. Application of chemical insecticides by the general public and professional pest managers is common, which means that Aprehend may be sprayed on existing insecticide residues. We evaluated the effect of chemical residues, of 22 different chemical insecticides on different household surface types. We found that residues from 12 chemical pesticides significantly reduced spore viability measured 5 weeks after application in comparison to the control. However, efficacy of Aprehend, as measured by bed bug mortality and mean survival time after exposure to sprayed surfaces, seven weeks after application was not impacted detrimentally. Furthermore, in some cases, efficacy of old chemical residues was enhanced by the combination of chemical and Aprehend seven weeks after application. Surface type also played a role in the relative efficacy of all products and combinations, particularly as the residues aged.